Public benefits of private technology adoption: The localized spatial externalities of water conservation in eastern Uttar Pradesh - Bhargava, Anil K.; Lybbert, Travis J.; Spielman, David J. (International Food Policy Research Institute, 2015)
With growing pressure on groundwater resources, water-conserving technologies (WCTs) look especially promising as a method of agricultural adaptation and poverty alleviation. While private benefits of WCTs are increasingly understood, public benefits are not as clear as they may seem. Some research has highlighted behavioral responses and diffusion as social consequences of private adoption. This paper focuses on the geophysical complications that shape public benefits across landscapes, raising spatial considerations of the WCT adoption decision and optimal diffusion patterns that can inform policymakers with the dual objectives of cost-efficient natural resource conservation and poverty alleviation, particularly in light of increasingly erratic weather patterns attributed to climate change. We focus on India—the world’s largest user of groundwater—and build a spatially sensitive hydroeconomic model to capture the dynamics of public water availability due to WCT adoption. We consider the spatial aspects of hydrological water flows, WCT adoption patterns, and public benefits of increased water access. We calibrate our model using a 2011 household-plot survey and estimates from a randomized control trial of a specific WCT in the country’s Gangetic Plains. Results show that early public benefits from WCTs occur primarily via reduced well interference when underground aquifers are large. Clustering of WCTs in this case can generate even higher benefits, suggesting localized spatial externalities of adoption. Policymakers interested in subsidizing or encouraging diffusion of key WCTs as a way to address both poverty alleviation and water conservation may thus consider both the private returns and public benefits presented here.